2018
DOI: 10.21307/jofnem-2018-021
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Carrot Cyst Nematode Heterodera carotae in Mexico: Morphological, Molecular Characterization, and Host Range Study

Abstract: During 2008 to 2016 in several nematological surveys in the Tepeaca Valley, Puebla, Mexico, carrot cyst nematode, Heterodera carotae was found parasitizing carrots, Daucus carota. The nematode was present in 61% of the sampled fields with high population densities, causing severe carrot yield losses in the Tepeaca Valley. The aim of this work was to study morphology, morphometrics, host range, and molecular characterization of the nematode. The morphological and morphometric characterization was made using lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
1
13
0
2
Order By: Relevance
“…n. Moreover, the nucleotide differences of these sequences with our new species sequences are also very low (2-4-bp difference for ITS and 0-1 bp for 28S). Previously, Escobar-Avila et al (2018) indicated that the sequences of H. goettingiana (HM370423 and HM370425) from Qinghai, China, might be a case of misidentification. Based on our phylogenetic and sequence analysis results, we regard Heterodera sp.…”
Section: Discussionmentioning
confidence: 99%
“…n. Moreover, the nucleotide differences of these sequences with our new species sequences are also very low (2-4-bp difference for ITS and 0-1 bp for 28S). Previously, Escobar-Avila et al (2018) indicated that the sequences of H. goettingiana (HM370423 and HM370425) from Qinghai, China, might be a case of misidentification. Based on our phylogenetic and sequence analysis results, we regard Heterodera sp.…”
Section: Discussionmentioning
confidence: 99%
“…Heterodera carotae is morphologically and genetically very close to the cabbage cyst nematode H. cruciferae , and the correct diagnosis is difficult and time consuming. rRNA and mitochondrial molecular markers such as ITS, cytochrome c oxidase 1 subunit ( coxI ) region (Vovlas et al , ; Escobar‐Avila et al , ) and coxI ‐derived primer sets (Madani et al , ) can help in the identification of members of the Goettingiana group, but none are able to provide an unequivocal distinction between H. carotae and H. cruciferae . As a result, only a host range test using carrot can distinguish these two species accurately (Escobar‐Avila et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…rRNA and mitochondrial molecular markers such as ITS, cytochrome c oxidase 1 subunit ( coxI ) region (Vovlas et al , ; Escobar‐Avila et al , ) and coxI ‐derived primer sets (Madani et al , ) can help in the identification of members of the Goettingiana group, but none are able to provide an unequivocal distinction between H. carotae and H. cruciferae . As a result, only a host range test using carrot can distinguish these two species accurately (Escobar‐Avila et al , ). The microsatellite markers used in the present study successfully amplified both H. carotae and H. cruciferae , and the high degree of genetic differentiation observed between reference H. carotae populations and reference H. cruciferae populations allowed H. carotae and H. cruciferae individuals to be clearly distinguished in the dataset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Como ocurre con todos los cultivos, la zanahoria es afectada por un gran número de patógenos, donde destacan, bacterias, hongos, virus, fitoplasmas y nematodos (Davis y Nuñez, 2007;Seo et al, 2015;Groves et al, 2020). El nematodo del quiste de la zanahoria (NQZ), Heterodera carotae Jones (1950a), es un patógeno que se encuentra distribuido en las zonas productoras de zanahoria en Europa, Norteamérica y África del Sur (Subbotin et al, 2010;Yu et al, 2017;Escobar-Avila et al, 2018;Handoo y Subbotin, 2018). Este NFQ tiene un rango limitado de hospedantes: zanahorias silvestres y cultivadas, y algunos miembros silvestres de la familia Apiaceae, como Torilis spp.…”
unclassified